Diseño y desarrollo de un simulador de código abierto para un robot submarino de propósito general - Corella-Solís, Eva (2021)
The project development in this thesis is a simulator for an underwater robot, which counts with 6 degrees of freedom, using ROS, Gazebo and UUV Simulator for his operation. For the development of the project, a 3D modeling and a mathematical physical modeling was created to adapt the submarine Kai, from El Grupo Integrado de Ingeniería, of the Universidad de la Coruña, to the vehicle implemented in the simulator. A world was also made for the submarine to operate in conditions like the real ones. The documentation and the results that validate this project are at the end of the document.